171k views
3 votes
Change y = – 2/3 x + 7 into standard form

User Kilokahn
by
4.3k points

1 Answer

5 votes

Answer:

2x + 3y = 42

Explanation:

Standard form should be like:

=> ax + by = c

To make an equation like the above one, we need to do the point-slope form first.

=> y - y1 = slope (x - x1)

Slope = -2/3

Y-intercept -> to find the y-intercept, we need to make the 'x' as 0.

=> y = -2/3 * 0 + 7

=> y = 7

X-intercept -> to find the x-intercept, we need to make 'y' as 0.

=> 0 = -2/3x + 7

=> -7 = -2/3x

=> -21/2 = -x

=> -10.5 = -x

=> 10.5 = x

So, x and y intercepts are 10.5 and 7.

We can now write the point-slope form:

=> y - 7 = -2/3 (x - 10.5)

=> y - 7 = -2/3x + 21/3

=> y = -2/3x + 7 + 7

=> y = -2/3x + 14

=> 2/3x + y = 14

=> Multiply all numbers by 3

=> 2x + 3y = 42

User Kevin Jose
by
5.9k points